‘On edge?’: Studies in precarious urbanisms - Philo, Chris; Parr, Hester; Söderström, Ola (My University, 2019)
This paper introduces the following Geoforum special issue on the theme of ‘Precarious Urbanisms’. Weaving into brief discussion of ‘precariousness’ and ‘precarity’, referencing the insights of Judith Butler, the paper reflects upon a distinctive move – characterising all of the eight papers comprising the special issue – whereby the entangled relations between precariousness and precarity play out in creating states and feelings of ‘on-edgeness’. This phrase encompasses the sense of peoples living ‘on the edge’, pushed to socio-spatial margins that may be literally peripheral, on the fringes of densely-populated (urban) sites of human inhabitation and activity, or more messily interstitial, found in the nooks, crannies and decaying or impermanent infrastructures of cities. Additionally, however, the phrase suggests the sense of peoples living ‘on edge’ – anxiously, fearfully, precariously – and whose ‘psychic topographies’, to borrow another term from Butler, may be mentally stressed and strained to and beyond breaking-points. As such, this special issue bridges across from classic (politicaleconomic) work on urban precarity to concerns addressed in the orbit of ‘mental health geographies’, tackling the making and possible unmaking of precariousness as an injurious way of being-in-the-world. Reference is made throughout this introduction to the other papers contributing to the special issue.
Keywords: Mental health geographies; On edge; On-edgeness; Precarity; Precariousness; Psychic topographies; Urbanisms